Antifungal activity of novel synthetic peptides by accumulation of reactive oxygen species (ROS) and disruption of cell wall against Candida albicans - Maurya, Indresh Kumar; Pathak, Sarika; Sharma, Monika; Sanwal, Hina; Chaudhary, Preeti; Tupe, Santosh; Deshpande, Mukund V.; Chauhan, Virander Singh; Prasad, Rajendra (Peptides, 2011)
In the present work, we investigated the antifungal activity of two de novo designed, antimicrobial peptides VS2 and VS3, incorporating unnatural amino acid alpha,beta-dehydrophenylalanine (Delta Phe). We observed that the low-hemolytic peptides could irreversibly inhibit the growth of various Candida species and multidrug resistance strains at MIC(80) values ranging from 15.62 mu M to 250 mu M. Synergy experiments showed that MIC(80) of the peptides was drastically reduced in combination with an antifungal drug fluconazole. The dye PI uptake assay was used to demonstrate peptide induced cell membrane permeabilization. Intracellular localization of the FITC-labeled peptides in Candida albicans was studied by confocal microscopy and FACS. Killing kinetics, PI uptake assay, and the intracellular presence of FITC-peptides suggested that growth inhibition is not solely a consequence of increased membrane permeabilization. We showed that entry of the peptide in Candida cells resulted in accumulation of reactive oxygen species (ROS) leading to cell necrosis. Morphological alteration in Candida cells caused by the peptides was visualized by electron microscopy. We propose that de novo designed VS2 and VS3 peptides have multiple detrimental effects on target fungi, which ultimately result in cell wall disruption and killing. Therefore, these peptides represent a good template for further design and development as antifungal agents. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Antifungal peptides; Candida albicans; Cell wall; ROS

Biochemical correlate of dimorphism in a zygomycete benjaminiella poitrasii: characterization of purified NAD-dependent glutamate dehydrogenase, a target for antifungal agents - Joshi, C. V.; Pathan, E. K.; Punekar, N. S.; Tupe, S. G.; Kapadnis, B. P.; Deshpande, Mukund V. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2013)
The fungal organisms, especially pathogens, change their vegetative (Y, unicellular yeast and H, hypha) morphology reversibly for survival and proliferation in the host environment. NAD-dependent glutamate dehydrogenase (NAD-GDH, EC 1.4.1.2) from a non-pathogenic dimorphic zygomycete Benjaminiella poitrasii was previously reported to be an important biochemical correlate of the transition process. The enzyme was purified to homogeneity and characterized. It is a 371 kDa native molecular weight protein made up of four identical subunits. Kinetic studies showed that unlike other NAD-GDHs, it may act as an anabolic enzyme and has more affinity towards 2-oxoglutarate than l-glutamate. Chemical modifications revealed the involvement of single histidine and lysine residues in the catalytic activity of the enzyme. The phosphorylation and dephosphorylation study showed that the NAD-GDH is present in active phosphorylated form in hyphal cells of B. poitrasii. Two of the 1,2,3 triazole linked beta-lactam-bile acid conjugates synthesized in the laboratory (B18, B20) were found to be potent inhibitors of purified NAD-GDH which also significantly affected Y-H transition in B. poitrasii. Furthermore, the compound B20 inhibited germ tube formation during Y-H transition in Candida albicans strains and Yarrowia lipolytica. The possible use of NAD-GDH as a target for antifungal agents is discussed.
Keywords: Antifungal agent; Benjaminiella poitrasii; Biochemical correlate of dimorphism; Candida albicans; NAD-GDH activity regulation; Yarrowia lipolytica; Yeast-hypha reversible transition

Mechanism of action of novel synthetic dodecapeptides against Candida albicans - Maurya, Indresh Kumar; Thota, Chaitanya Kumar; Sharma, Jyotsna; Tupe, Santosh Genba; Chaudhary, Preeti; Singh, Manoj Kumar; Thakur, Indu Shekhar; Deshpande, Mukund V.; Prasad, Rajendra; Chauhan, Virander Singh (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Three de novo designed low molecular weight cationic peptides (IJ2, IJ3 and IJ4) containing an unnatural amino acid alpha,beta-didehydrophenylalanine (APhe) exhibited potent antifungal activity against fluconazole (FLC) sensitive and resistant clinical isolates of Candida albicans as well as non-albi cans and other yeast and filamentous pathogenic fungi. In the present study, their synthesis, susceptibility of different fungi and the mechanism of anti-candidal action have been elucidated. Methods: The antimicrobial peptides (AMPs) were synthesized by solid-phase method and checked for antifungal activity against different yeasts and fungi by broth microdilution method. Anti-candidal mode of action of the peptides was investigated through detecting membrane permeabilization by confocal microscopy, Reactive Oxygen Species (ROS) generation by fluorometry, apoptosis and necrosis by flow cytometry and cell wall damage using Scanning and Transmission Electron Microscopy. Results and conclusions: The MIC of the peptides against C. albicans and other yeast and filamentous fungal pathogens ranged between 3.91 and 250 mu M. All three peptides exhibited effect on multiple targets in C. albi cans including disruption of cell wall structures, compromised cell membrane permeability leading to their enhanced entry into the cells, accumulation of ROS and induction of apoptosis. The peptides also showed synergistic effect when used in combination with fluconazole (FLC) and caspofungin (CAS) against C. albi cans. General significance: The study suggests that the AMPs alone or in combination with conventional antifungals hold promise for the control of fungal pathogens, and need to be further explored for treatment of fungal infections. (C) 2013 Elsevier By. All rights reserved.
Keywords: Antifungal peptide; Antimicrobial peptide (AMP); Apoptosis; Candida albicans; Reactive Oxygen Species (ROS)

Possible mechanism of antifungal phenazine-1-carboxamide from pseudomonas sp against dimorphic fungi Benjaminiella poitrasii and human pathogen Candida albicans - Tupe, S. G.; Kulkarni, R. R.; Shirazi, F.; Sant, D. G.; Joshi, Swati P.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2015)
AimInvestigation of antifungal mechanism of phenazine 1-carboxamide (PC) produced by a Pseudomonas strain MCC2142. Methods and ResultsAn antifungal metabolite produced by a Pseudomonas was purified and identified as PC. Human pathogenic fungi such as Candida albicans, Candidaglabrata, Cryptococcus neoformans, Fusarium oxysporum, Aspergillus fumigatus and Aspergillus niger were found to be inhibited by PC (MIC90 32-64gml(-1)). Addition of PC (20gml(-1)) during yeast (Y)-hypha (H) transitions inhibited germ tube formation by >90% and >99% in C.albicans National Collection of Industrial Microorganisms (NCIM) 3471 and nonpathogenic model Benjaminiella poitrasii, respectively. After exposure to PC (20gml(-1)), 75-80% yeast cells of B.poitrasii and C.albicans NCIM 3471 showed rhodamine 123 fluorescence indicating high intracellular reactive oxygen species (ROS) production. ROS further led to hyperpolarization of mitochondrial membrane, subsequently induction of apoptosis as evident by externalization of phosphatidylserine, DNA fragmentation, chromatin condensation and finally death in B.poitrasii. In C.albicans NCIM 3471, PC (20gml(-1)) induced apoptosis. ConclusionsThe antifungal effect of PC in B.poitrasii and C.albicans may be due to ROS-mediated apoptotic death. Significance and Impact of the StudyInhibition of Y-H transition of B.poitrasii and C.albicans by PC indicates that it may prove useful in the control of dimorphic human pathogens.
Keywords: Apoptosis; Candida albicans; dimorphism; phenazines; Pseudomonas sp; reactive oxygen species

Silicon incorporated morpholine antifungals: design, synthesis, and biological evaluation - Jachak, Gorakhnath R.; Ramesh, Remya; Sant, Duhita G.; Jorwekar, Shweta U.; Jadhav, Manjusha R.; Tupe, Santosh G.; Deshpande, Mukund V.; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2015)
Known morpholine class antifungals (fenpropimorph, fenpropidin, and amorolfine) were synthetically modified through silicon incorporation to have 15 sila-analogues. Twelve sila-analogues exhibited potent antifungal activity against different human fungal pathogens such as Candida albicans, Candida glabrata, Candida tropicalis, Cryptococcus neoformans, and Aspergillus niger. Si la-analogue 24 (fenpropimorph analogue) was the best in our hands, which showed superior fungicidal potential than fenpropidin, fenpropimorph, and amorolfine. The mode of action of sila-analogues was similar to morpholines, i.e., inhibition of sterol reductase and sterol isomerase enzymes of ergosterol synthesis pathway.
Keywords: Antifungal drugs; Candida albicans; ergosterol biosynthesis; morpholines; sila-analogues